Inorganic millstone and preparation method thereof

By combining modified sisal fiber with specific aggregates, the problem of insufficient strength and wear resistance of inorganic grinding stones has been solved, and high-strength and wear-resistant inorganic grinding stones have been prepared, providing a reliable decorative material for high-load scenarios.

CN121318312APending Publication Date: 2026-01-13HEBEI QIANBAO SPECIAL CEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511579744.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing inorganic grinding stones suffer from insufficient strength and poor wear resistance during long-term use, especially in high-load and high-frequency use scenarios, where they are prone to cracking and wear. Existing improvement methods have failed to effectively solve the problems of interface bonding and matrix density.

Method used

Modified sisal fiber and a specific aggregate combination, including calcined oyster shell powder, silica-modified ceramic powder and slag powder, are used to enhance the strength and wear resistance of inorganic grinding stone through multi-dimensional synergistic effects. The modified sisal fiber is treated with alkali, coated with titanium carbide and treated with silane coupling agent to improve its bonding strength with cement.

Benefits of technology

It significantly improves the flexural strength and wear resistance of inorganic grinding stones, extends their service life, and reduces maintenance frequency and costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of inorganic millstone preparation, and particularly discloses an inorganic millstone and a preparation method thereof. The inorganic millstone comprises cement, sand, aggregate, modified sisal fibers, glass, color pigment and a water reducing agent, the aggregate comprises calcined oyster powder, silicon dioxide modified ceramic powder and slag powder, and the modified sisal fibers are prepared by sequentially carrying out alkali treatment, titanium carbide coating and silane coupling agent treatment on sisal fibers. According to the inorganic millstone provided by the invention, the aggregate components and the fiber components are optimized, so that the prepared inorganic millstone has excellent strength and wear resistance, and a new idea is provided for preparation of the inorganic millstone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic grinding stone preparation technology, and in particular to an inorganic grinding stone and its preparation method. Background Technology

[0002] Inorganic terrazzo, with its advantages of seamless decoration, stain resistance, and easy cleaning, is widely used for floor and wall decoration in commercial complexes, industrial plants, transportation hubs, and other places. Especially in high-traffic, high-load environments, stringent requirements are placed on its mechanical strength and surface abrasion resistance. However, existing inorganic terrazzo products generally suffer from insufficient strength and poor abrasion resistance during long-term use. Specifically, the floor is prone to cracking under heavy loads, edge chipping, surface wear and sanding after high-frequency friction, and loss of gloss. This not only shortens the lifespan of the terrazzo but also requires frequent maintenance and repair, increasing usage costs.

[0003] The main reasons for the poor strength and wear resistance of existing inorganic grinding stones are as follows: On the one hand, traditional aggregates often use ordinary quartz sand, marble particles, etc. These aggregates either have low hardness and are difficult to resist long-term friction; and the interfacial bonding between the aggregate and the cementitious matrix is ​​poor, easily forming micropores. Under stress, stress concentration easily occurs at the pores, leading to macroscopic cracks. On the other hand, the reinforcing fibers commonly used in existing inorganic grinding stones have obvious shortcomings. Glass fibers have poor compatibility with the cement matrix, and the reinforcing effect is limited due to insufficient interfacial bonding. Although unmodified synthetic fibers have good toughness, their low hardness cannot help improve wear resistance, and they are prone to agglomeration during mixing, forming local weak points. Currently, some researchers have improved wear resistance by increasing the amount of aggregate or replacing it with high-hardness aggregates, but the problems of interfacial bonding and matrix density have not been solved, and it is still impossible to balance strength and wear resistance. Some researchers have also tried to fill the pores by adding nanoparticles, but nanoparticles are prone to agglomeration and are difficult to disperse evenly, thus limiting the improvement effect. Therefore, there is an urgent need to provide an inorganic grinding stone with high strength and excellent wear resistance to meet the long-term service requirements of high-load and high-frequency use scenarios. Summary of the Invention

[0004] Therefore, the present invention provides an inorganic grinding stone and a method for preparing the same. The inorganic grinding stone provided by the present invention optimizes the aggregate and fiber components, resulting in an inorganic grinding stone with excellent strength and wear resistance.

[0005] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows: The present invention provides an inorganic grinding stone, comprising the following components in parts by weight: 25-35 parts cement, 40-50 parts sand, 18-22 parts aggregate, 10-15 parts modified sisal fiber, 12-15 parts glass, 6-8 parts colored pigment, and 2-5 parts water-reducing agent. The aggregates include calcined oyster shell powder, silica-modified ceramic powder, and slag powder; The modified sisal fiber was prepared by sequentially subjecting sisal fiber to alkali treatment, titanium carbide coating, and silane coupling agent treatment.

[0006] Compared to existing technologies, the inorganic grinding stone provided by this invention uses aggregates and modified sisal fibers as core reinforcing components. Through multi-dimensional synergistic effects with cement, sand, and water-reducing agents, it significantly improves the wear resistance and strength of the inorganic grinding stone. Specifically, the calcined oyster shell powder in the aggregate contains highly active calcium oxide, which provides an alkaline environment for the entire inorganic grinding stone. This activates the pozzolanic activity of the vitreous body in the slag powder, promoting a secondary hydration reaction between the inorganic components in the slag powder and the calcium hydroxide formed in the early stages of cement hydration. This results in the formation of more dense CSH gel, which fills the micropores inside the cement stone. This process further forms a dense microstructure, thereby improving the strength and wear resistance of the inorganic grinding stone. In addition, the calcium ions released by calcined oyster powder can react with the silica in the silica-modified ceramic powder, avoiding the problem of interfacial fracture in the inorganic grinding stone during use due to poor compatibility between the ceramic powder and the cement matrix. The addition of silica-modified ceramic powder can further improve the wear resistance of the inorganic grinding stone. Furthermore, the silica coating on the surface of the silica-modified ceramic powder can further improve the bonding force between the ceramic powder and the cement product, further improving the strength and wear resistance of the inorganic grinding stone.

[0007] In modified sisal fibers, alkali treatment creates a rough texture on the fiber surface, increasing the titanium carbide coating and improving the contact area between the modified sisal fibers and cement, thus enhancing the performance of the inorganic grinding stone. The titanium carbide coating further imparts excellent hardness and wear resistance to the fibers, thereby improving the wear resistance and strength of the inorganic grinding stone. Furthermore, silane coupling agent treatment significantly increases the binding of the modified sisal fibers with calcium ions and CSH gel in cement hydration products, further improving the bonding force between the sisal fibers and cement, thus increasing the strength of the inorganic grinding stone. In addition, sisal fibers modified in specific ways can prevent the generation and propagation of cracks, avoiding the problems of decreased strength and increased wear caused by crack extension.

[0008] Preferably, the cement is white silicate cement with a whiteness ≥90 and a compressive strength ≥42.5MPa.

[0009] The whiteness of white silicate cement was tested according to the national standard GB / T 2015-2017 "White Silicate Cement".

[0010] Preferably, the particle size of the sand is 0.55~0.75mm.

[0011] Preferably, the colored pigment includes at least one of phthalocyanine pigment, azo pigment, or indigo pigment.

[0012] Preferably, the water-reducing agent includes a polycarboxylate water-reducing agent.

[0013] Preferably, the mass ratio of calcined oyster powder, silica-modified ceramic powder and slag powder in the aggregate is 1:(1.2~1.5):(0.8~1).

[0014] Preferably, the particle size of the calcined oyster powder is 4-6 mm.

[0015] Preferably, the calcined oyster powder is obtained by calcining oyster powder at 750~800℃.

[0016] More preferably, the calcination time is 2 to 2.5 hours.

[0017] The calcination of oyster powder at different temperatures and times has a significant impact on the performance of inorganic grinding stones. Through a large number of experiments, the inventors screened out the optimal calcination temperature and time, which significantly improved the strength and wear resistance of inorganic grinding stones.

[0018] Preferably, the particle size of the silica-modified ceramic powder is 1~3mm.

[0019] Preferably, the preparation method of the silica-modified ceramic powder includes the following steps: Step a: Add tetraethyl orthosilicate, silane coupling agent and ceramic powder to alcohol solvent, adjust pH to acidic conditions, ultrasonically disperse and impregnate, separate solid and liquid, dry to obtain primary processed ceramic powder; Step b: The primary processed ceramic powder is heated to 500~520℃ and calcined to obtain the silica-modified ceramic powder.

[0020] The method for preparing silica-modified ceramic powder provided by this invention is simple to operate, easy to industrialize and mass-produce, and the modified ceramic powder has stable performance, which can efficiently meet the needs of inorganic grinding stone aggregates and improve the wear resistance and strength of inorganic grinding stone.

[0021] Preferably, in step a, the alcohol solvent is ethanol.

[0022] Preferably, in step a, the silane coupling agent is KH-560.

[0023] Preferably, in step a, the mass ratio of tetraethyl orthosilicate, silane coupling agent, ceramic powder and alcohol solvent is (3~4):(0.5~1):(3~4):100.

[0024] It should be further noted that in step a, acidic conditions refer to a pH of 4 to 5.

[0025] Preferably, in step a, the ultrasonic dispersion power is 200~300W and the time is 30~40min.

[0026] Preferably, in step a, the immersion temperature is 35~45℃ and the time is 7~8h.

[0027] Preferably, in step b, the calcination time is 3-4 hours.

[0028] Preferably, the specific surface area of ​​the slag powder is 500~550 m². 2 / kg.

[0029] Preferably, the method for preparing the modified sisal fiber includes the following steps: Step 1: Impregnate sisal fibers in an alkaline solution, separate solids and liquids, and dry to obtain alkaline-treated sisal fibers; Step 2: Add titanium salt and carbon source to water, adjust pH to acidic, and obtain precursor solution; Step 3: Disperse the alkali-treated sisal fibers in the precursor solution, impregnate, separate the solid and liquid, and calcine to obtain primary modified sisal fibers; Step 4: Add the silane coupling agent to the ethanol solution to obtain the silane coupling agent solution; Step 5: Disperse the modified sisal fiber in a silane coupling agent solution, impregnate, separate the solid and liquid, and dry to obtain the modified sisal fiber.

[0030] The modified sisal fiber preparation method provided by this invention can obtain modified sisal fibers stably coated with titanium carbide without complicated equipment. It is not only simple to operate, but also ensures that the modified sisal fibers have high toughness, wear resistance and good compatibility, thereby greatly improving the performance of inorganic grinding stones.

[0031] Preferably, in step 1, the sisal fiber has a length of 3-6 mm and a diameter of 20-40 µm.

[0032] Preferably, in step 1, the mass concentration of the alkaline solution is 5% to 6%.

[0033] More preferably, in step 1, the alkaline solution is an aqueous solution of sodium hydroxide.

[0034] Preferably, in step 1, the ratio of sisal fiber to alkaline solution is 1g:(10~12)mL.

[0035] Preferably, in step 1, the immersion temperature is 60~65℃ and the time is 2~2.5h.

[0036] It should be further noted that in step 1, the impregnation process also requires stirring, with a stirring rate of 300~350 r / min.

[0037] Preferably, in step 1, the drying temperature is 60~80℃ and the time is 6~8h.

[0038] Preferably, in step 2, the titanium salt is titanium chloride.

[0039] Preferably, in step 2, the carbon source is glucose.

[0040] Preferably, in step 2, the mass ratio of the titanium salt to the carbon source is 1:(0.6~0.7).

[0041] Preferably, in step 2, the concentration of the titanium salt in water is 0.1~0.3 mol / L.

[0042] Preferably, in step 2, the acidic condition is a pH value of 2 to 3.

[0043] It should be further noted that in step 2, when adding titanium salt to water, it is necessary to ensure that it is added under cold water conditions.

[0044] Preferably, in step 3, the ratio of the amount of alkali-treated sisal fiber to the precursor solution is 1g:(8~9)mL.

[0045] Preferably, in step 3, the dispersion is ultrasonic dispersion with a power of 300~320W and a time of 15~18min.

[0046] Preferably, in step 3, the soaking time is 2 to 2.5 hours.

[0047] Preferably, in step 3, the calcination temperature is 800~820℃.

[0048] Preferably, in step 3, the temperature is increased to 800-820°C at a heating rate of 5-6°C / min.

[0049] More preferably, in step 3, the calcination time is 60-80 minutes.

[0050] It should be further noted that in step 3, calcination is carried out under an inert atmosphere.

[0051] It should be further noted that in step 3, drying is required before calcination.

[0052] Preferably, the mass ratio of silane coupling agent to primary modified sisal fiber is (0.2~0.4):1.

[0053] Preferably, in step 4, the silane coupling agent is γ-aminopropyltriethoxysilane.

[0054] Preferably, in step 4, the mass concentration of the ethanol solution is 1% to 2%.

[0055] It should be further noted that in step 4, the pH of the silane coupling agent solution also needs to be adjusted to 4-4.5.

[0056] Preferably, in step 5, the immersion temperature is 60~70℃ and the time is 1~2h.

[0057] This invention provides a method for preparing the above-mentioned inorganic grinding stone, comprising the following steps: The weighed cement, sand, aggregate, modified sisal fiber, glass, colored pigment and water-reducing agent are mixed evenly to obtain inorganic grinding stone.

[0058] This invention, through the rational design of the composition of inorganic grinding stone, in which aggregate and modified sisal fiber serve as core reinforcing components, significantly improve the wear resistance and strength of inorganic grinding stone through multi-dimensional synergistic effects with cement, sand, and water-reducing agents, providing a new approach to the preparation of inorganic grinding stone. Detailed Implementation

[0059] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0060] The whiteness of silicate cement is 92, and its compressive strength is 42.5 MPa. The polycarboxylate superplasticizer was purchased from Jinan Meifu Chemical Technology Co., Ltd.

[0061] To better illustrate the present invention, further examples are provided below.

[0062] Example 1 This embodiment provides an inorganic grinding stone, comprising the following components in parts by weight: 25 parts silicate cement, 40 parts sand with a particle size of 0.55mm, 20 parts aggregate, 10 parts modified sisal fiber, 12 parts glass, 8 parts azo pigment, and 2 parts polycarboxylate superplasticizer. The aggregate consists of calcined oyster shell powder in a mass ratio of 1:1.5:1, silica-modified ceramic powder with a particle size of 1-3 mm, and aggregate with a specific surface area of ​​500 m². 2 / kg of slag powder; Among them, calcined oyster powder with a particle size of 4~6mm is obtained by calcining oyster powder at 750℃ for 2.5h.

[0063] The preparation method of silica-modified ceramic powder includes the following steps: Step a: Add tetraethyl orthosilicate, KH-560 and ceramic powder to ethanol, adjust pH to 4, ultrasonically disperse at 200W for 40 min, impregnate at 35℃ for 8 h, separate solid and liquid, and dry to obtain primary processed ceramic powder; the mass ratio of tetraethyl orthosilicate, KH-560, ceramic powder and ethanol is 4:1:4:100. Step b: Heat the primary processed ceramic powder to 500°C and calcine for 3 hours to obtain the silica-modified ceramic powder.

[0064] The preparation method of modified sisal fiber includes the following steps: Step 1: Add sisal fibers with a length of 3 mm and a diameter of 20 µm to a 5% sodium hydroxide aqueous solution and immerse them at 60°C for 2.5 h. During immersion, stir at a rate of 300 r / min. Separate the solid and liquid components and dry them at 60°C for 6 h to obtain alkali-treated sisal fibers. The ratio of sisal fibers to alkali solution is 1 g: 10 mL. Step 2: Add titanium chloride and glucose to cold water in sequence, adjust the pH to 3, and obtain the precursor solution; the mass ratio of titanium chloride to glucose is 1:0.6, and the concentration of titanium chloride in cold water is 0.1 mol / L; Step 3: The alkali-treated sisal fiber was ultrasonically dispersed in the precursor solution at a power of 320W for 18 minutes. It was then impregnated at room temperature for 2.5 hours, followed by solid-liquid separation and drying. The temperature was then increased to 800℃ at a rate of 5℃ / min and calcined under a nitrogen atmosphere for 60 minutes to obtain the primary modified sisal fiber. The ratio of alkali-treated sisal fiber to precursor solution was 1g:8mL. Step 4: Add γ-aminopropyltriethoxysilane to a 1% ethanol solution and adjust the pH to 4 to obtain a silane coupling agent solution; the mass ratio of γ-aminopropyltriethoxysilane to the primary modified sisal fiber is 0.2:1. Step 5: The modified sisal fiber is ultrasonically dispersed in a silane coupling agent solution, impregnated at 60°C for 2 hours, separated from the solid, and dried to obtain the modified sisal fiber.

[0065] This embodiment also provides a method for preparing the above-mentioned inorganic grinding stone, including the following steps: The weighed silicate cement, sand, aggregate, modified sisal fiber, glass, azo pigment and polycarboxylate superplasticizer are mixed evenly to obtain inorganic grinding stone.

[0066] Example 2 This embodiment provides an inorganic grinding stone, comprising the following components in parts by weight: 30 parts silicate cement, 45 parts sand with a particle size of 0.75mm, 18 parts aggregate, 15 parts modified sisal fiber, 15 parts glass, 6 parts azo pigment, and 5 parts polycarboxylate superplasticizer. The aggregate consists of calcined oyster shell powder in a mass ratio of 1:1.4:0.8, silica-modified ceramic powder with a particle size of 1-3 mm, and aggregate with a specific surface area of ​​530 m². 2 / kg of slag powder; Among them, calcined oyster powder with a particle size of 4~6mm is obtained by calcining oyster powder at 800℃ for 2h.

[0067] The preparation method of silica-modified ceramic powder includes the following steps: Step a: Add tetraethyl orthosilicate, KH-560 and ceramic powder to ethanol, adjust pH to 5, ultrasonically disperse at 300W for 30 min, impregnate at 45℃ for 7 h, separate solid and liquid, and dry to obtain primary processed ceramic powder; the mass ratio of tetraethyl orthosilicate, KH-560, ceramic powder and ethanol is 3:0.5:4:100. Step b: Heat the primary processed ceramic powder to 520°C and calcine for 4 hours to obtain the silica-modified ceramic powder.

[0068] The preparation method of modified sisal fiber includes the following steps: Step 1: Add sisal fibers with a length of 6 mm and a diameter of 30 µm to a 5% sodium hydroxide aqueous solution and immerse them at 65°C for 2 hours. During immersion, stir at a rate of 350 r / min. Separate the solid and liquid components and dry them at 80°C for 8 hours to obtain alkali-treated sisal fibers. The ratio of sisal fibers to alkali solution is 1 g: 12 mL. Step 2: Add titanium chloride and glucose to cold water in sequence, adjust the pH to 2, and obtain the precursor solution; the mass ratio of titanium chloride to glucose is 1:0.7, and the concentration of titanium chloride in cold water is 0.3 mol / L; Step 3: The alkali-treated sisal fiber was ultrasonically dispersed in the precursor solution at a power of 300W for 15 minutes. After immersion at room temperature for 2 hours, the solid and liquid were separated, dried, and heated to 820℃ at a heating rate of 6℃ / min. The mixture was then calcined in a nitrogen atmosphere for 80 minutes to obtain the primary modified sisal fiber. The ratio of alkali-treated sisal fiber to precursor solution was 1g:8mL. Step 4: Add γ-aminopropyltriethoxysilane to a 1% ethanol solution and adjust the pH to 4.5 to obtain a silane coupling agent solution; the mass ratio of γ-aminopropyltriethoxysilane to the primary modified sisal fiber is 0.4:1. Step 5: The modified sisal fiber is ultrasonically dispersed in a silane coupling agent solution, impregnated at 70°C for 1 hour, separated from the solid, and dried to obtain the modified sisal fiber.

[0069] This embodiment also provides a method for preparing the above-mentioned inorganic grinding stone, including the following steps: The weighed silicate cement, sand, aggregate, modified sisal fiber, glass, azo pigment and polycarboxylate superplasticizer are mixed evenly to obtain inorganic grinding stone.

[0070] Example 3 This embodiment provides an inorganic grinding stone, comprising the following components in parts by weight: 35 parts silicate cement, 50 parts sand with a particle size of 0.6 mm, 22 parts aggregate, 12 parts modified sisal fiber, 12 parts glass, 6 parts azo pigment, and 5 parts polycarboxylate superplasticizer. The aggregate consists of calcined oyster shell powder in a mass ratio of 1:1.2:0.8, silica-modified ceramic powder with a particle size of 1-3 mm, and aggregate with a specific surface area of ​​550 m². 2 / kg of slag powder; Among them, calcined oyster powder with a particle size of 4~6mm is obtained by calcining oyster powder at 760℃ for 2h.

[0071] The preparation method of silica-modified ceramic powder includes the following steps: Step a: Add tetraethyl orthosilicate, KH-560 and ceramic powder to ethanol, adjust pH to 5, ultrasonically disperse at 250W for 35min, impregnate at 40℃ for 7.5h, separate solid and liquid, and dry to obtain primary processed ceramic powder; the mass ratio of tetraethyl orthosilicate, KH-560, ceramic powder and ethanol is 3:1:3:100. Step b: Heat the primary processed ceramic powder to 500°C and calcine for 4 hours to obtain the silica-modified ceramic powder.

[0072] The preparation method of modified sisal fiber includes the following steps: Step 1: Add 5 mm long and 40 µm diameter sisal fibers to a 5% sodium hydroxide aqueous solution and immerse at 65°C for 2 h. Stir at 320 r / min during immersion. Separate the solid and liquid, and dry at 70°C for 8 h to obtain alkali-treated sisal fibers. The ratio of sisal fibers to alkali solution is 1 g: 12 mL. Step 2: Add titanium chloride and glucose to cold water in sequence, adjust the pH to 3, and obtain the precursor solution; the mass ratio of titanium chloride to glucose is 1:0.7, and the concentration of titanium chloride in cold water is 0.3 mol / L; Step 3: Disperse the alkali-treated sisal fiber in the precursor solution using ultrasonication at 300W for 15 min, impregnate at room temperature for 2 h, separate the solid and liquid, dry, heat to 810℃ at a heating rate of 6℃ / min, and calcine under nitrogen atmosphere for 70 min to obtain primary modified sisal fiber; the ratio of alkali-treated sisal fiber to precursor solution is 1 g: 9 mL. Step 4: Add γ-aminopropyltriethoxysilane to a 1% ethanol solution and adjust the pH to 4.5 to obtain a silane coupling agent solution; the mass ratio of γ-aminopropyltriethoxysilane to the primary modified sisal fiber is 0.4:1. Step 5: The modified sisal fiber is ultrasonically dispersed in a silane coupling agent solution, impregnated at 65°C for 1 hour, separated from the solid, and dried to obtain the modified sisal fiber.

[0073] This embodiment also provides a method for preparing the above-mentioned inorganic grinding stone, including the following steps: The weighed silicate cement, sand, aggregate, modified sisal fiber, glass, azo pigment and polycarboxylate superplasticizer are mixed evenly to obtain inorganic grinding stone.

[0074] Comparative Example 1 This comparative example provides an inorganic grinding stone that differs from Example 1 in that: the silica-modified ceramic powder is replaced with an equal amount of ceramic powder; the other steps and components are the same as in Example 1.

[0075] Comparative Example 2 This comparative example provides an inorganic grinding stone, which differs from Example 1 in that the preparation method of the modified sisal fiber is different. The preparation method of the modified sisal fiber includes the following steps: Step 1: Add sisal fibers with a length of 3 mm and a diameter of 20 µm to a 5% sodium hydroxide aqueous solution and immerse them at 60°C for 2.5 h. During immersion, stir at a rate of 300 r / min. Separate the solid and liquid components and dry them at 60°C for 6 h to obtain alkali-treated sisal fibers. The ratio of sisal fibers to alkali solution is 1 g: 10 mL. Step 2: Add titanium chloride and glucose to cold water in sequence, adjust the pH to 3, and obtain the precursor solution; the mass ratio of titanium chloride to glucose is 1:0.6, and the concentration of titanium chloride in cold water is 0.1 mol / L; Step 3: The alkali-treated sisal fiber was ultrasonically dispersed in the precursor solution at a power of 320W for 18 minutes. It was then impregnated at room temperature for 2.5 hours, followed by solid-liquid separation and drying. The temperature was then increased to 800℃ at a rate of 5℃ / min and calcined under a nitrogen atmosphere for 60 minutes to obtain modified sisal fiber. The ratio of alkali-treated sisal fiber to precursor solution was 1g:8mL. The other steps and ingredients are the same as in Example 1.

[0076] Comparative Example 3 This comparative example provides an inorganic grinding stone, which differs from Example 1 in that the modified sisal fiber is replaced with an equal amount of modified basalt fiber; specifically, it includes the following steps: Step 1: Add basalt fibers with a length of 3 mm and a diameter of 20 µm to a 5% sodium hydroxide aqueous solution and immerse them at 60°C for 2.5 h. During immersion, stir at a rate of 300 r / min. Separate the solid and liquid components and dry them at 60°C for 6 h to obtain alkali-treated basalt fibers. The ratio of basalt fibers to alkali solution is 1 g: 10 mL. Step 2: Add titanium chloride and glucose to cold water in sequence, adjust the pH to 3, and obtain the precursor solution; the mass ratio of titanium chloride to glucose is 1:0.6, and the concentration of titanium chloride in cold water is 0.1 mol / L; Step 3: The alkali-treated basalt fiber was ultrasonically dispersed in the precursor solution at a power of 320W for 18 minutes. It was then impregnated at room temperature for 2.5 hours, followed by solid-liquid separation and drying. The temperature was then increased to 800℃ at a rate of 5℃ / min and calcined under a nitrogen atmosphere for 60 minutes to obtain primary modified basalt fiber. The ratio of alkali-treated basalt fiber to precursor solution was 1g:8mL. Step 4: Add γ-aminopropyltriethoxysilane to a 1% ethanol solution and adjust the pH to 4 to obtain a silane coupling agent solution; the mass ratio of γ-aminopropyltriethoxysilane to primary modified basalt fiber is 0.2:1. Step 5: The modified basalt fiber is ultrasonically dispersed in a silane coupling agent solution, impregnated at 60°C for 2 hours, separated from the solid, and dried to obtain the modified basalt fiber. The other steps and ingredients are the same as in Example 1.

[0077] Comparative Example 4 This comparative example provides an inorganic grinding stone, which differs from Example 1 in that: slag powder is replaced with an equal amount of fly ash; The other steps and ingredients are the same as in Example 1.

[0078] Example of effect The raw material formulations in Examples 1-3 and Comparative Examples 1-4 were mixed with water evenly (mass ratio of 100:12) and then tested.

[0079] Flexural strength was determined according to GB / T 50784-2013; Wear resistance was tested according to JC / T 421-2004. The specific test results are shown in Table 1: Table 1

[0080] As shown in Table 1, the inorganic grinding stone provided in this embodiment of the invention has excellent compressive strength and wear resistance, with a flexural strength of 18.9 MPa and an abrasion value as low as 0.0185 g / cm. 2The flexural strength and abrasion resistance of the inorganic grinding stones prepared in Comparative Examples 1-4 of this invention are significantly lower than those of the inorganic grinding stone prepared in Example 1. This invention, by optimizing the aggregate and fiber components, produces inorganic grinding stones with excellent strength and abrasion resistance, providing a new approach to the preparation of inorganic grinding stones.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An inorganic grinding stone, characterized in that, The components include the following parts by weight: 25-35 parts cement, 40-50 parts sand, 18-22 parts aggregate, 10-15 parts modified sisal fiber, 12-15 parts glass, 6-8 parts colored pigment, and 2-5 parts water-reducing agent. The aggregates include calcined oyster shell powder, silica-modified ceramic powder, and slag powder; The modified sisal fiber was prepared by sequentially subjecting sisal fiber to alkali treatment, titanium carbide coating, and silane coupling agent treatment.

2. The inorganic grinding stone as described in claim 1, characterized in that, The mass ratio of calcined oyster powder, silica-modified ceramic powder and slag powder in the aggregate is 1:(1.2~1.5):(0.8~1).

3. The inorganic grinding stone as described in claim 1 or 2, characterized in that, The calcined oyster powder is obtained by calcining oyster powder at 750~800℃; The particle size of the calcined oyster powder is 4~6mm.

4. The inorganic grinding stone as described in claim 1 or 2, characterized in that, The preparation method of the silica-modified ceramic powder includes the following steps: Step a: Add tetraethyl orthosilicate, silane coupling agent and ceramic powder to alcohol solvent, adjust pH to acidic conditions, ultrasonically disperse and impregnate, separate solid and liquid, dry to obtain primary processed ceramic powder; Step b: The primary processed ceramic powder is heated to 500~520℃ and calcined to obtain the silica-modified ceramic powder.

5. The inorganic grinding stone as described in claim 4, characterized in that, In step a, the silane coupling agent is KH-560; In step a, the mass ratio of tetraethyl orthosilicate, silane coupling agent, ceramic powder and alcohol solvent is (3~4):(0.5~1):(3~4):100; In step a, the immersion temperature is 35~45℃ and the time is 7~8h; In step b, the calcination time is 3-4 hours.

6. The inorganic grinding stone as described in claim 1 or 2, characterized in that, The specific surface area of ​​the slag powder is 500~550m². 2 / kg.

7. The inorganic grinding stone as described in claim 1, characterized in that, The preparation method of the modified sisal fiber includes the following steps: Step 1: Immerse sisal fibers in an alkaline solution, separate solids and liquids, and dry to obtain alkaline-treated sisal fibers; Step 2: Add titanium salt and carbon source to water, adjust pH to acidic, and obtain precursor solution; Step 3: Disperse the alkali-treated sisal fibers in the precursor solution, impregnate, separate the solid and liquid, and calcine to obtain primary modified sisal fibers; Step 4: Add the silane coupling agent to the ethanol solution to obtain the silane coupling agent solution; Step 5: Disperse the modified sisal fiber in a silane coupling agent solution, impregnate, separate the solid and liquid, and dry to obtain the modified sisal fiber.

8. The inorganic grinding stone as described in claim 7, characterized in that, In step 1, the sisal fibers have a length of 3-6 mm and a diameter of 20-40 µm; In step 1, the ratio of sisal fiber to alkaline solution is 1g:(10~12)mL, and the mass concentration of the alkaline solution is 5%~6%. In step 1, the immersion temperature is 60~65℃ and the time is 2~2.5h; In step 2, the titanium salt is titanium chloride; In step 2, the carbon source is glucose; In step 2, the acidic condition is: pH value of 2~3; In step 2, the mass ratio of the titanium salt to the carbon source is 1:(0.6~0.7). In step 2, the concentration of the titanium salt in water is 0.1~0.3 mol / L.

9. The inorganic grinding stone as described in claim 7, characterized in that, In step 3, the ratio of the amount of alkali-treated sisal fiber to the precursor solution is 1g:(8~9)mL; In step 3, the soaking time is 2~2.5 hours; In step 3, the calcination temperature is 800~820℃; In step 3, the calcination time is 60-80 minutes; The mass ratio of silane coupling agent to primary modified sisal fiber is (0.2~0.4):1; In step 4, the silane coupling agent is γ-aminopropyltriethoxysilane; In step 5, the immersion temperature is 60~70℃ and the time is 1~2h.

10. A method for preparing an inorganic grinding stone according to any one of claims 1 to 9, characterized in that, Includes the following steps: The weighed cement, sand, aggregate, modified sisal fiber, glass, colored pigment and water-reducing agent are mixed evenly to obtain inorganic grinding stone.